DEVELOPMENT OF AN ISLAMIC EDUCATIONAL INFOGRAPHIC ANIMATION VIDEO ON INTERNET DANGERS FOR CHILDREN UNDER TEN - Fadhilah, Cut; Safira, Ulfa; Muhammad (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2025)
This study developed an Islamic educational infographic animation video aimed at raising awareness among parents and educators about the dangers of internet use for children under ten years old. Utilizing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the research involved needs analysis, storyboard creation, animation production, and effectiveness testing. The video, which integrates Islamic moral values with engaging visual storytelling, addresses key risks such as digital addiction, exposure to inappropriate content, and lack of supervision. The effectiveness of the video was evaluated through pre-test and post-test questionnaires administered to 40 selected respondents, supported by qualitative interviews. The results showed a statistically significant improvement in participants' understanding (p < 0.05), with over 80% reporting increased readiness to guide children in safe and responsible digital behavior. Respondents also appreciated the video’s simple language, appealing visuals, and clear message delivery. This study contributes to the field of digital parenting and Islamic education by offering a culturally relevant, faith-integrated educational tool. Future research is encouraged to enhance interactivity and widen dissemination across digital platforms to reach broader audiences. Penelitian ini mengembangkan video animasi infografis edukatif berbasis nilai-nilai Islam yang bertujuan untuk meningkatkan kesadaran orang tua dan pendidik mengenai bahaya penggunaan internet pada anak-anak di bawah usia sepuluh tahun. Dengan menggunakan model ADDIE (Analisis, Desain, Pengembangan, Implementasi, dan Evaluasi), penelitian ini mencakup analisis kebutuhan, pembuatan storyboard, produksi animasi, serta pengujian efektivitas. Video ini mengintegrasikan nilai-nilai moral Islam dengan narasi visual yang menarik, dan membahas risiko utama seperti kecanduan digital, paparan konten tidak pantas, serta kurangnya pengawasan. Efektivitas video dievaluasi melalui kuesioner pre-test dan post-test yang diberikan kepada 40 responden terpilih, serta didukung oleh wawancara kualitatif. Hasilnya menunjukkan peningkatan pemahaman yang signifikan secara statistik (p < 0.05), dengan lebih dari 80% responden menyatakan peningkatan kesiapan dalam membimbing anak menggunakan internet secara aman dan bertanggung jawab. Responden juga mengapresiasi penggunaan bahasa yang sederhana, visual yang menarik, serta penyampaian pesan yang jelas. Penelitian ini memberikan kontribusi dalam bidang parenting digital dan pendidikan Islam dengan menawarkan alat edukasi yang relevan secara budaya dan terintegrasi dengan nilai keimanan. Penelitian selanjutnya disarankan untuk meningkatkan interaktivitas serta memperluas distribusi melalui berbagai platform digital agar menjangkau audiens yang lebih luas.